Cardiovascular effects of the intracerebroventricular injection of adrenomedullin: roles of the peripheral vasopressin and central cholinergic systems - Cam-Etoz,B. (2012)
Our objective was to investigate in conscious Sprague-Dawley (6-8 weeks, 250-300 g) female rats (N = 7 in each group) the effects of intracerebroventricularly (icv) injected adrenomedullin (ADM) on blood pressure and heart rate (HR), and to determine if ADM and calcitonin gene-related peptide (CGRP) receptors, peripheral V1 receptors or the central cholinergic system play roles in these cardiovascular effects. Blood pressure and HR were observed before and for 30 min following drug injections. The following results were obtained: 1) icv ADM (750 ng/10 µL) caused an increase in both blood pressure and HR (DMAP = 11.8 ± 2.3 mmHg and ΔHR = 39.7 ± 4.8 bpm). 2) Pretreatment with a CGRP receptor antagonist (CGRP8-37) and ADM receptor antagonist (ADM22-52) blocked the effect of central ADM on blood pressure and HR. 3) The nicotinic receptor antagonist mecamylamine (25 µg/10 µL, icv) and the muscarinic receptor antagonist atropine (5 µg/10 µL, icv) prevented the stimulating effect of ADM on blood pressure. The effect of ADM on HR was blocked only by atropine (5 µg/10 µL, icv). 4) The V1 receptor antagonist [β-mercapto-β-β-cyclopentamethylenepropionyl¹, O-me-Tyr²,Arg8]-vasopressin (V2255; 10 µg/kg), that was applied intravenously, prevented the effect of ADM on blood pressure and HR. This is the first study reporting the role of specific ADM and CGRP receptors, especially the role of nicotinic and muscarinic central cholinergic receptors and the role of peripheral V1 receptors in the increasing effects of icv ADM on blood pressure and HR.